Devilry, deviance, and public sphere: the social discovery of moral panic in eighteenth century London - Hamerton, Christopher (Palgrave Macmillan, 2023)
Devilry, Deviance, and Public Sphere draws on criminology and social theory to explore and expand social historical themes in the analysis of perceptions of deviance and crime in the eighteenth century. Developing the theoretical device of Folk Devils and Moral Panics, instigated by Stanley Cohen and developed by Erich Goode and Nachman Ben-Yehuda, the book explores the social discovery of, and public response to, crime and deviance in that period. Detailed contemporary case studies of youth violence, sexual deviance, and substance abuse are used to argue that Hanoverian London and its novel media can be identified as the initiating historical site for what might now be termed public order moral panics. In doing so, Hamerton provides a vivid historical lineage of moral panic which traverses much of the long eighteenth century. The book considers social change, allowing for points of theoretical convergence and divergence to be observed, whilst exploring historical models of public opinion, media, deviance and crime alongside the unique character and power located within the burgeoning Metropolis. Devilry, Deviance, and Public Sphere seeks to make an important contribution to the understanding of both moral panic theory and the historiography of crime and deviance, and posits that the current discourse on folk devils and moral panics can be extended and enriched via the exploration of the moral crises of earlier centuries